Students’ Self-Adjustment with Boarding School Environment in MAN Insan Cendekia Lubuk Alung - Batubara, Juliana; Darwin, Darwin; Ikhwanuddin, Ikhwanuddin (Institut Agama Islam Negeri Imam Bonjol Padang, 2021)
This research aims to describe and compare the self-adjustment of boarding school students with the school environment in terms of gender (comparative descriptive study of students at MAN Insan Cendekia Lubuk Alung, West Sumatra). This type of research is descriptive-comparative with a questionnaire instrument. The population of all students of class X, sampling with purposive random sampling technique in order to obtain a sample of 82 students. Data were analyzed by descriptive statistical analysis, and to test the differences used t test. The results showed that in general the self-adjustment of boarding school students with the school environment of MAN Insan Cendekia Lubuk Alung, West Sumatra was classified high and there was a significance difference from the self-adjustment of male and female students. Therefore, school counselors can provide various types of counseling and guidance services to students of MAN Insan Cendekia Lubuk Alung, West Sumatra so that they are able to overcome difficulties in their self-adjustment by fostering self-confidence and training students how to adapt to the new environment and atmosphere in accordance with the rules